2022
DOI: 10.3233/wor-210346
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and stress: An evaluation using Beck’s depression and anxiety inventory among college students and faculty members of Jouf University

Abstract: BACKGROUND: Individuals might suffer emotional, psychological, and even bodily challenges as a result of any pandemic. The impact of the COVID-19 outbreak on Saudi Arabian University students and faculty members has received little attention. OBJECTIVE: To assess stress during the COVID-19 pandemic among university college students and faculty members of Jouf University, KSA and evaluate the impact of socio- demographic factors on anxiety and depression levels. METHODS: Two hundred and seventeen participants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…While faculty strived to provide education contingency in support of students' academic growth, faculty in the current study reported to have undergone heightened levels of stress and even depression. Heightened levels of stress among educators during the pandemic were actually observed in numerous studies originated from countries all over the world such as China, India, Israel, Italy, Poland and the United States [18,31,[33][34][35][36][37][38]. The main reasons were the time-consuming course preparation for online teaching and lack of confidence as well as competencies in technology utilization.…”
Section: Discussionmentioning
confidence: 99%
“…While faculty strived to provide education contingency in support of students' academic growth, faculty in the current study reported to have undergone heightened levels of stress and even depression. Heightened levels of stress among educators during the pandemic were actually observed in numerous studies originated from countries all over the world such as China, India, Israel, Italy, Poland and the United States [18,31,[33][34][35][36][37][38]. The main reasons were the time-consuming course preparation for online teaching and lack of confidence as well as competencies in technology utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The SAS and SDS have good internal consistency and can be used to measure depression and anxiety. Moreover, previous studies have used the SAS (Wang Z. H. et al, 2020), SDS (Tong Li et al, 2021), BAI and BDI (Ganji et al, 2022) to assess the impact of the COVID-19 pandemic on the mental health of college students. Hence, in the current study, all participants completed these scales to assess the severity of symptoms of depression and anxiety.…”
Section: Questionnaire Analysismentioning
confidence: 99%
“…The main trigger of depression is hopelessness which is defined by symptoms of decreased motivation, sadness, suicide, decreased energy, psychomotor retardation, sleep disturbances, poor concentration, and negative cognition (Akdemir et al, 2022;Cao et al, 2022;Fuligni, Chiang, & Tottenham, 2021). According to hopelessness theory, low self-esteem or beliefs about a life event will have significant long-term consequences that can instil a sense of hopelessness, expressed in a specific set of depressive symptoms called hopelessness depression (Cao et al, 2022;Chutipattana et al, 2022;Ganji et al, 2022).…”
Section: Study Pressure In Universitymentioning
confidence: 99%
“…Despair is also referred to as a negative emotional response in individuals when they cannot achieve the goal/target, and naturally, they will feel a psychological collision within themselves. Desperate individuals seem to behave sluggishly, rigidly, stupidly, and reluctantly to engaging in activities (Cao et al, 2022;Ganji et al, 2022). This feeling of hopelessness makes the individual's natural pressure increase.…”
Section: Introductionmentioning
confidence: 99%